A note on work in progress: secondary articulation in Thai stops - Rischel, Jørgen; Thavisak, Amon (Annual Report of the Institute of Phonetics University of Copenhagen, 1984)
The present paper outlines the system of obstruents in Modern Central Thai and points out various controversial issues having to do with laryngeal control and supralaryngeal secondary articulation. Some very preliminary findings concerning Thai /p t/ are mentioned, and it is shown with fiberoptic illustrations how the epiglottis is crucially involved in an articulatory gesture found with these consonants in certain environments.